Ideological, Social and Cultural Aspects of Events 2014
DOI: 10.1079/9781780643526.0086
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Liverpool European Capital of Culture 2008.

Abstract: This chapter draws on Turner's concept of 'the subjunctive mood' in order to understand how local people performed identities in the period 2008-2009, when Liverpool held the title of European Capital of Culture 2008. The chapter considers both the transformation of individuals/communities and also larger scale transformation. It is argued that performances of local identities are dependent on the structures and norms of the dominant narrative and the perceived myths and stereotypes of the city.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Once a wealthy centre of trade in the 19th century, then globally recognized for its music culture in the 1960s, it became a city in serious economic and social decline by the late 1970s. The city has experienced investment in regeneration projects since the 1980s, such as the development of the International Garden Festival in 1984, the renewal of the Albert Docks as a tourist attraction, through to the European Capital of Culture in 2008 (a wide range of studies explore the changes the city has seen, for example, Belchem, 2006;Bianchini and Parkinson, 1993;Kokosalakis et al, 2006;Munck, 2003;Platt, 2015;Sykes et al, 2013). These highs and lows contribute not only to how outsiders understand Liverpool, but also how local people understand and perform their own identities (Boland, 2008(Boland, , 2010Platt, 2014).…”
Section: Placemaking In Liverpool and The Role Of Womenmentioning
confidence: 99%
“…Once a wealthy centre of trade in the 19th century, then globally recognized for its music culture in the 1960s, it became a city in serious economic and social decline by the late 1970s. The city has experienced investment in regeneration projects since the 1980s, such as the development of the International Garden Festival in 1984, the renewal of the Albert Docks as a tourist attraction, through to the European Capital of Culture in 2008 (a wide range of studies explore the changes the city has seen, for example, Belchem, 2006;Bianchini and Parkinson, 1993;Kokosalakis et al, 2006;Munck, 2003;Platt, 2015;Sykes et al, 2013). These highs and lows contribute not only to how outsiders understand Liverpool, but also how local people understand and perform their own identities (Boland, 2008(Boland, , 2010Platt, 2014).…”
Section: Placemaking In Liverpool and The Role Of Womenmentioning
confidence: 99%
“…Indeed, Davis () found that the relationship between place and festival was highly relevant but codependent. For example, European Capital of Culture or UK City of Culture designations have had an impact of challenging perceptions of places (Boland, Murtagh, & Shirlow, ; Garcia, ; Platt, ). Additionally, even just bidding for the awards brings some positive outcomes (Wilson & O'Brien, ).…”
Section: Contribution Of Urban Festivals To Place Image Place‐brandimentioning
confidence: 99%